The Effectiveness of Incentives on Staff Retention and Happiness at Workplace (International Journal of Food and Nutritional Sciences, 2022)
Using rewards and perks in managing human resources is a successful strategy for retaining employees and motivating individuals. This study looked at how compensation and benefits affected employee retention and motivation. The goals were to assess the benefits and extent of remuneration and the connection between causes among workers and retention. Simple methods of random sampling were applied in this article. Data collection was done using the questionnaire. Fifty questionnaires were correctly completed, respondents' responses were presented in frequency tables, and demographic information was calculated using basic percentages; the chi-square (X2) technique for data analysis was used to test the validity of the hypotheses. This study also shows how remuneration and benefits can create and maintain an edge over others for the organization.